2013
DOI: 10.1111/ejn.12366
|View full text |Cite
|
Sign up to set email alerts
|

Central nesfatin‐1 influences the excitability of ghrelin‐responsive gastric distension neurons in the arcuate nucleus and reduces gastric motility in rats

Abstract: Although the novel satiety peptide nesfatin-1 has been shown to regulate gastric motility, the underlying mechanisms have yet to be elucidated. The study aimed to explore the effects of nesfatin-1 on ghrelin-responsive gastric distension (GD) neurons in the arcuate nucleus (Arc), and potential regulation mechanisms of gastric motility by the paraventricular nucleus (PVN). Single-unit discharges in the Arc were recorded extracellularly, and gastric motility in conscious rats was monitored during the administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Forty rats were prepared for GD following the protocol mentioned above, and the electrophysiological recording procedure was based on the previously described method (Li et al, 2013). The anesthetized rats were bound on a stereotaxic frame, and craniotomy was performed around the coordinates: −2.5 mm posterior to Bregma and 0.8 mm lateral.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty rats were prepared for GD following the protocol mentioned above, and the electrophysiological recording procedure was based on the previously described method (Li et al, 2013). The anesthetized rats were bound on a stereotaxic frame, and craniotomy was performed around the coordinates: −2.5 mm posterior to Bregma and 0.8 mm lateral.…”
Section: Methodsmentioning
confidence: 99%
“…Further, the receptor for nesfatin-1 is yet unknown, making a mechanistic understanding of nesfatin-1 signaling in the central nervous system difficult to ascertain. To begin to answer these questions, we have injected nesfatin-1 in PVN and ARC (Li et al, 2013; Guo et al, 2015), and found that nesfatin-1 signaling in these areas has an inhibitory role in gastric motility. Moreover, these effects were caused by nesfatinergic projections from lateral hypothalamic area (LHA) to PVN or from PVN to ARC.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the abdominal cavity was exposed and contractile force transducers were sutured onto the serosa of the gastric antrum, 0.5 cm caudal to the pyloric ring, to measure circular muscle motility [14] . The lead wires of the force transducers were tunneled subcutaneously and exteriorised at the nape of the neck, protruding 2-3 cm through a small incision between the scapulae [14] . Following this, the abdomen was closed with suture and the animals were allowed to recover for 4 days before administrating chemicals.…”
Section: Animal Surgerymentioning
confidence: 99%
“…Verification of the correct position of administration site was performed by injection of Pontamine sky blue (2μL) at the end of the recording of gastric motility [14] . After perfusion and fixation of the brain, 50 μm frozen coronal sections were cut through the regions of the LHA, stained with Neutral Red and observed under a light microscope [14] .…”
Section: Histological Verificationmentioning
confidence: 99%
See 1 more Smart Citation